(untitled) (Jurnal Bahasa, 2014)
The aim of this cross-sectional survey is to identify the prevalence of learning-disabled children who have language and communication disorders. Besides that, this study also investigates the general and specific symptoms of language and communication disorders in these children. The study applied the adaptive sampling technique and involved 1125 special-education children from 56 integrated schools in Kelantan. The Speech or Language Impairment Checklist of Hannell, with a 4-point Likert scale, was used to collect the data, which was gleaned from the children’s profile documents, observations of their behaviour and interview with parents. The study found that 6 per cent (n=67) of the children in the study were considered as having difficulty with verbal communication. When comparing the mean score, the general symptom "Delay in learning to communicate" is the most common symptom of communication disorder. Therefore, it is recommended that teachers who teaching such students use augmentative and alternative communication (AAC) to optimize students’ understanding. Keywords: special education, communication disorders, cross-sectional study, learning disabilities, oral communication